Haemodynamic Interplay Between Concomitant Left Ventricular Outflow Tract Obstruction and Aortic Stenosis - Priya Bansal (Radcliffe Medical Media, 2021)
The authors describe a patient with hypertrophic cardiomyopathy with concomitant left ventricular outflow tract obstruction and aortic stenosis. Detailed haemodynamic assessment of the serial lesions was performed. Alcohol septal ablation resulted in a significant reduction of gradients across the left ventricular outflow tract.